A Strong Impact of Soil Tetracycline on Physiology and Biochemistry of Pea Seedlings. (10th January 2019) - Margas, Małgorzata; Piotrowicz-Cieślak, Agnieszka I.; Michalczyk, Dariusz J.; Głowacka, Katarzyna
Abstract : Antibiotics are a new type of contaminants found in the environment. They are increasingly used in farm animal production systems and may accumulate in crops, limiting the plant growth rate and nutritive value. The aim of this study was to determine the effects of tetracycline (TC) on physiological and biochemical properties of pea seedlings. The presence of TC in the soil during 24 hours did not result in any distinct changes of the seedlings. However, after five days (120 h) of soil TC action, the seedling appearance and metabolic activities were significantly affected. Leaves lost their green coloration as a result of a 38% degradation of their chlorophyll. Total protein was isolated from shoots of pea grown for 120 h in TC-supplemented perlite (250 mg × L −1 ) or perlite with no TC (control plants). The 2D electrophoretic maps of proteins from non-TC shoots contained 326 spots, whereas maps of shoot proteins from TC-treated seedlings contained only 316 spots. The identity of 26 proteins was determined. The intensity of most proteins (62%) increased. This was particularly visible with diphosphate kinase, superoxide dismutase [Cu-Zn], peroxiredoxin, and glutathione S-transferase. A distinctly increased quantity of a protein involved in photosynthesis (photosystem II stability/assembly factor HCF136) was also noted. One protein was detected only in shoots of TC-treated plants (as opposed to controls); however, it could not be identified. Moreover, at the highest concentration of TC (250 mg × L −1 of perlite), a sharp increase in free-radical content was observed along with the amount of callose deposited in vascular bundles of leaves and roots and the occurrence of masses of dead cells in roots. It was found, therefore, that tetracycline which has been known for inhibiting predominantly the attachment of aminoacyl-tRNA to the ribosomal acceptor in bacteria can disturb diverse metabolic pathways in plants.